2009
DOI: 10.1002/eat.20716
|View full text |Cite
|
Sign up to set email alerts
|

Does avoidant personality disorder impact on the outcome of treatment for bulimia nervosa?

Abstract: These findings suggest AVPD is not a significant predictor of BN outcome. However, AVPD is associated with poorer psychiatric symptoms although much of this variance appears to be attributable to the lifetime presence of any mood disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…A further consideration is that the outcome of BN may not be affected by the presence of any PD regardless of diagnosis or severity. Our results concur with findings from analyses on the same data set that examined the impact of borderline PD and avoidant PD on outcome and found no long-term effect of these personality features on eating disorder symptoms or diagnosis, psychosocial functioning, or depressive symptoms [23,35]. This adds to the growing body of research that shows no long-term impact of PDs on the outcome of BN [20,36,37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A further consideration is that the outcome of BN may not be affected by the presence of any PD regardless of diagnosis or severity. Our results concur with findings from analyses on the same data set that examined the impact of borderline PD and avoidant PD on outcome and found no long-term effect of these personality features on eating disorder symptoms or diagnosis, psychosocial functioning, or depressive symptoms [23,35]. This adds to the growing body of research that shows no long-term impact of PDs on the outcome of BN [20,36,37].…”
Section: Discussionsupporting
confidence: 88%
“…Finally, although we found that Tyrer's model suggested that severity of personality pathology does not affect outcome in eating disorders, other methods of classifying PD severity need to be examined, for example, total PD symptoms. Although PD severity does not affect the course of an eating disorder, there is still conflicting evidence about whether the nature of the PD may do so [23,35,44]. Further replication of this study is needed to establish the validity of Tyrer's dimensional personality classification for those with eating disorders and comorbid Axis II disorders.…”
Section: Discussionmentioning
confidence: 78%
“…At 3‐year follow‐up, the impact of co‐morbid AvPD was found to be associated with greater psychosocial and psychiatric impairment: Hamilton Depression Rating Scale (HDRS: F (2, 109) = 3.8, p = 0.03, AvPD > no PD) and Global Assessment of Functioning (GAF: F (2, 109) = 3.4, p = 0.04, AvPD > no PD). However, there were no significant differences in binge/purge frequency between those with or without PD ( p > 0.05) (Rowe et al, 2010). Therefore, in spite of ED symptoms in those with AvPD improving to the same extent as other PD and no PD groups, they continued to experience higher levels of impairment in terms of psychosocial functioning and depression at 3‐year follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…There is a general agreement in the literature that more motivation to change is a predictor of better outcome at the end of treatment and at follow‐up (Clausen, Lübeck, & Jones, 2013; Gregertsen, Mandy, Kanakam, Armstrong, & Serpell, 2019; Mansour et al, 2012; Richard et al, 2005; Vall & Wade, 2015). Some studies (Clausen et al, 2013; Mansour et al, 2012) emphasize the importance of “autonomous motivation” which is similar to the term “intrinsic motivation.” Regarding disordered personality, a diagnosis of personality disorders was a predictor of poor follow‐up outcome in some studies (Rossiter, Agras, Telch, & Schneider, 1993; Steinhausen, 2002; Vall & Wade, 2015), but no predictor in other studies (Fichter & Quadflieg, 1997; Rowe et al, 2010). Our analyses including motivation to change and personality were also inconclusive, with personality being a predictor for BN only, and motivation to change not functioning as a predictor of diagnostic outcome.…”
Section: Discussionmentioning
confidence: 98%